A comparative study of phenols composition, antioxidant, and antifungal potency of leaves extract from five Moroccan Vitis vinifera L. varieties. Issue 2 (27th December 2019) - Jediyi, Hicham; Naamani, Khalid; Ait Elkoch, Abderrahim; Dihazi, Abdelhey; Lemjiber, Naima
Abstract: Vitis vinifera (L) crops, covers an area of about 54, 000 ha corresponding to a production of 230, 000 t of grapes, representing 5.5% of the national perennial corps. However, this plant is sensitive to various ravages and diseases, among others, the cryptogrammic by fungi. The degrading enzymes of the cell wall are among the factors of pathogenicity the more important than fungi use to colonize their host plants. In this study, the first step was devoted to the antioxidant activity and phenols composition (phenylalanine‐ammonia‐lyase [PAL], tyrosine‐ammonia‐lyase [TAL], flavonoids, and tannins) as well as high‐performance liquid chromatography analysis in five vineyard leaves extract, which are "Superior, Early sweet and Flame" (Allochthonous), "Abbou and Adari" (endemic). In the second step, the lytic activities "pectinase, polygalacturonase, xylanase, mannanase, glucanase, and cellulase" were investigated among six epiphytic fungus to compare their hydrolytic aggressiveness. Subsequently, as a third part, phenols antifungal potency and Trichoderma biocontrol were displayed in the study. The phenolic compounds observed in the attributes leaves were different among varieties ( p < .05), and show that the endemic variety "Abbou" leads the phytochemical amount, which has the highest quantities of PAL, and TAL, as well as the DPPH and FRAP antioxidant activity, while the introduced variety show a higher amount in total phenol and flavonoids. The polygalacturonase, mannanase, and pectinase activities are probably the main factors responsible for the aggressiveness of the studied fungus. Phenols potency showed a good mycelial inhibition with 82.09% as compared to the biocontrol (64.45%). Given the efficacy of the phytochemical control in this study, the phenols could be a part of integrated management strategies for sustainable control of vineyard disease. Abstract : The polygalacturonase, mannanase and pectinase activities are probably the main factors responsible for the aggressiveness of the studied fungus. The phenols potency showed a good mecylial inhibition with 82.089% as compared to the bio‐control (64.45%). Given the efficacy of the phytochemical‐control, the phenols could be a part of a novel multi‐component control strategy for a better vineyard disease management.